Dampak Literasi Digital pada Perilaku Pencegahan Phishing: Literature Review - Nastiti Aura Istiqomah; Naza Aprilia Lorenza; Fitri Mutia (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The advancement of technology has brought about ease and efficiency, but along with these benefits, a multitude of complexities and risks have also arisen, Among these complexities, threats to cyber security are of utmost concern. This paper zeros in on phishing as one of the most widespread forms of digital data theft. The aim of the paper is to explore the role of digital literacy in predicting phishing behavioral responses. The research methodologies employed in this study is systematised literature review (SLR) which incorporates the methodology of collecting, analysing and synthesising previous works in the field to develop research findings. This particular review focuses on 18 articles published between the years 2014 and 2024, the review indicates that digital literacy substantially influences individuals’ capacity to prevent phising incidents. The various ramifications of phishing include monetary losses, social and security ramifications, damage to privacy and media information as well as psychological harm to the affected individuals. Phishing cybercrimes has been the primary reason for the digital literacy outreach initiatives to help the public improve their skills and understand the importance of protecting their data. Efforts to strengthen prevention may include integrating digital literacy into education curricula, conducting continuous employee raining, and adopting AI-based detection systems. Strengthening digital literacy in the outreach programs is essential to reducing the risk of phishing cybercrimes.